Sociological and political aspects of intellectuals in the contemporary society: - Intellectuals in the interpretation of Čedomir Čupić - - Jovović, Zoran (Political Life, 2025)
The aim of this paper is, first of all, to consider sociologically and politically the importance of intellectuals in contemporary society in correlation with desirable qualities such as trust and honesty. Therefore, in addition to trust and honesty, which should adorn a true intellectual, the paper is focused on the interpretation of relationships: intellectuals and institutions, intellectuals and reality, intellectuals and education, intellectuals and forms of violence, intellectuals and the masses, and intellectuals and the secret service. Except for the mentioned relationships, the paper discusses two types of intellectuals: critical and salon intellectuals, as well as the influence of intellectuals on the formation of cultural patterns in society and the state. In conclusion, it is stated that, in addition to trust, honesty should be an attribute of every true intellectual. It implies the existence of objectivity and impartiality towards: the other, others and the environment, but also morals and moral values.